2022
DOI: 10.1111/jdi.13811
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of glucose time in range and area under curve in range in relation to risk of diabetic retinopathy in type 2 diabetes patients

Abstract: Aims/introduction We proposed a novel continuous glucose monitoring (CGM)‐based metric, area under the curve in range (AucIR), for integrating both the amplitude and duration of dysglycemia, and further compared AucIR with the emerging key CGM‐derived metric, time in range (TIR). Materials and methods A total of 2,030 adult patients with type 2 diabetes were enrolled during May 2020 to October 2021. AucIR and TIR were measured with 7‐day CGM data. Logistic regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…[ 10 ] A cross-sectional study comprising 3262 patients with type 2 diabetes found that TIR was significantly linked to all stages of diabetic retinopathy after adjusting for covariates including HbA1c. [ 21 ] Mayeda et al previously demonstrated that less TIR was correlated with a higher risk of diabetic peripheral neuropathy (DPN) assessed using the Michigan Neuropathy Screening Instrument questionnaire in patients with type 2 diabetes and concomitant chronic kidney disease. [ 22 ] In contrast, there was no significant association between HbA1c and DPN symptoms in their study population.…”
Section: Relationship Between Tir and Diabetes-related Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 10 ] A cross-sectional study comprising 3262 patients with type 2 diabetes found that TIR was significantly linked to all stages of diabetic retinopathy after adjusting for covariates including HbA1c. [ 21 ] Mayeda et al previously demonstrated that less TIR was correlated with a higher risk of diabetic peripheral neuropathy (DPN) assessed using the Michigan Neuropathy Screening Instrument questionnaire in patients with type 2 diabetes and concomitant chronic kidney disease. [ 22 ] In contrast, there was no significant association between HbA1c and DPN symptoms in their study population.…”
Section: Relationship Between Tir and Diabetes-related Outcomesmentioning
confidence: 99%
“…For instance, the area under the curve in range (AucIR), which integrates both the amplitude and duration of dysglycemia, has been compared with TIR. [ 47 ] Although AucIR was significantly associated with DR, it did not provide more benefits over TIR. Other metrics such as the Glycemia Risk Index (GRI) [ 48 ] and the comprehensive glucose pentagon [ 49 ] have been put forward.…”
Section: Future Directions Of Tirmentioning
confidence: 99%
See 2 more Smart Citations
“…However, since the influence of glycemia depends on both the duration and the glucose levels, indices that reflect both variables are expected to predict retinopathy better than the conventional glycemic indices. A recent attempt using the ‘area under the curve in range’ was unable to demonstrate a significant association with retinopathy 5 . Nevertheless, further research of similar indices for detailed glycemic status using the new technology is expected.…”
mentioning
confidence: 95%